Phylogenetic relationships and population structure of Portunus pelagicus in the coastal waters of Malaysia inferred from mitochondrial DNA and microsatellites - Chai, Chuan Jian (2017)
The abundance of blue swimmer crabs, Portunus pelagicus throughout the Indo-West Pacific region makes it a valuable target species for fishery industry. The increasing demands of P. pelagicus have led to a growing interest on the broodstock selection of this particular crab species. This study examined the phylogenetic relationships, demographic history and population structure of P. pelagicus through sequence analyses of mitochondrial cytochrome c oxidase I (COI) gene (600 bp) as well as fragment analyses of four pairs of microsatellite loci. A total of 109 crab samples were collected from five different populations throughout the coastal areas of Malaysia. These include Perak (Pantai Remis and Kuala Sepetang), Johor (Pendas), Negeri Sembilan (Port Dickson), Terengganu (Besut) and Sarawak (Bako).